Jalaluddin Rumi's Thoughts Regarding the Concept of Love as a Basis for Religious Moderation - Syah, Yoshy Hendra Hardiyan; Rosyad, Rifki (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
This article examines Jalaluddin Rumi's thoughts on the concept of love as the basis for religious moderation. This article originates from a literature review or literature review to explain descriptively and discuss Jalaluddin Rumi's thoughts on the concept of love as the basis for religious moderation. In this article, the approach used is the Philosophical-Sufistic approach to the thoughts brought by Rumi, namely the concept of love. Jalaluddin Rumi answered and thoroughly discussed the concept of love as the basis for religious moderation in the book